1995
DOI: 10.1002/j.1460-2075.1995.tb07019.x
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct regions of FC gamma RI initiate separate signalling pathways involved in endocytosis and phagocytosis.

Abstract: Cross‐linking of the high affinity receptor for IgG, Fc gamma RI, can result in both endocytosis of immune complexes and phagocytosis of opsonized particles in myeloid cells, although the cytoplasmic domain of the receptor lacks the tyrosine activation motif which has been implicated in signal transduction triggered by cross‐linking of other Fc receptors. To identify the structural determinants of Fc gamma RI‐mediated ligand internalization, we have expressed Fc gamma RI or truncated versions of Fc gamma RI in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 24 publications
6
79
1
Order By: Relevance
“…The ␥-chain cytoplasmic domain contains immunoreceptor tyrosine-based activation motifs (ITAMs) and the ␥-chain cytoplasmic domain is both necessary and sufficient for Fc␥RI␣-induced functions (33,34). Biochemical studies have shown that both cross-linking of Fc⑀RI␣-␥-chain complex and the Fc␥RI␣-␥-chain complex result in activation of Src family kinases and the tyrosine kinase p72 Syk (4,(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…The ␥-chain cytoplasmic domain contains immunoreceptor tyrosine-based activation motifs (ITAMs) and the ␥-chain cytoplasmic domain is both necessary and sufficient for Fc␥RI␣-induced functions (33,34). Biochemical studies have shown that both cross-linking of Fc⑀RI␣-␥-chain complex and the Fc␥RI␣-␥-chain complex result in activation of Src family kinases and the tyrosine kinase p72 Syk (4,(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the capacity of monocytes and macrophages to internalize IgG-opsonized substrates (23)(24)(25), the mechanism of antigenic modulation promoted by monocytes has been generally presumed to be due to internalization of IgG Ab/target Ag immune complexes by the cancer cells, rather than by monocytes.…”
Section: T Argeting Of Ags On Cancer Cells By Mabs Has Been a Key Strmentioning
confidence: 99%
“…8A) (47). Phagocytosis is characterized by sequential phosphorylation of cellular proteins mediated by Src and Syk kinases (66), whereas simple endocytosis of small Ab-Ag complexes does not require tyrosine kinase action (23). Based on these considerations, we propose the following mechanism for shaving.…”
Section: Role Of Fc␥r In the Mechanism Of Shavingmentioning
confidence: 99%
See 1 more Smart Citation
“…This association is not a prerequisite for transient receptor expression but is necessary for stable expression (11,12). The ␥-chain cytoplasmic domain contains an immunoreceptor tyrosine activation motif (ITAM) and current data suggest that the ␥-chain cytoplasmic domain is both necessary and sufficient for Fc␥RIa induced functions (13)(14)(15). Biochemical studies have shown that cross-linking of the Fc␥RIa⅐␥-chain complex results in activation of a Src family kinase(s) and the tyrosine kinase p72…”
mentioning
confidence: 99%